2015
DOI: 10.3389/fvets.2015.00068
|View full text |Cite
|
Sign up to set email alerts
|

Cystoisospora suis – A Model of Mammalian Cystoisosporosis

Abstract: Cystoisospora suis is a coccidian species that typically affects suckling piglets. Infections occur by oral uptake of oocysts and are characterized by non-hemorrhagic transient diarrhea, resulting in poor weight gain. Apparently, primary immune responses to C. suis cannot readily be mounted by neonates, which contributes to the establishment and rapid development of the parasite, while in older pigs age-resistance prevents disease development. However, the presence of extraintestinal stages, although not unequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 104 publications
(129 reference statements)
0
32
0
3
Order By: Relevance
“…Moreover, the number of AF countable excretion days, the AUC for OpG, the maximum individual OpG as well as the mean OpG from SD 9 to 19 was comparable between the control and treatment groups of this isolate, indicating complete drug resistance. The above mentioned parameters For quantitative evaluation of the fecal score only the period of mean values >1.00 was evaluated for study days [9][10][11][12][13][14][15][16][17][18] tended to be higher in groups Holl-Ctrl, Holl-20 and Holl-30 compared to group Wien-Ctrl, and the prepatent period for excretion detected by AF technique was shorter in Holland-I compared to Wien-I. Variations in prepatent periods can be attributed not only to factors such as infection dose or age and health of piglets (which were comparable between all groups) but also to the virulence of C. suis isolates [7,45,46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the number of AF countable excretion days, the AUC for OpG, the maximum individual OpG as well as the mean OpG from SD 9 to 19 was comparable between the control and treatment groups of this isolate, indicating complete drug resistance. The above mentioned parameters For quantitative evaluation of the fecal score only the period of mean values >1.00 was evaluated for study days [9][10][11][12][13][14][15][16][17][18] tended to be higher in groups Holl-Ctrl, Holl-20 and Holl-30 compared to group Wien-Ctrl, and the prepatent period for excretion detected by AF technique was shorter in Holland-I compared to Wien-I. Variations in prepatent periods can be attributed not only to factors such as infection dose or age and health of piglets (which were comparable between all groups) but also to the virulence of C. suis isolates [7,45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Isospora suis) is the most pathogenic species of swine coccidian and most severely affects suckling piglets [1][2][3][4]. Clinical signs include pasty to watery non-hemorrhagic diarrhea, weight loss and ill thrift [5][6][7][8][9][10]. At present, cystoisosporosis is considered as one of the leading causes of diarrhea in neonatal piglets with high prevalences worldwide [3,7,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Our study aims to investigate determinants of both Ancylostoma (nematode) and Cystoisospora (coccidian) infection loads in high‐ranking and low‐ranking juvenile spotted hyenas and to assess the resistance and tolerance of juveniles in these two social categories to parasite infection. We focus on Ancylostoma and Cystoisospora because both have direct life cycles that need no intermediary host, both cause damage to the epithelial lining of the small intestine, and are considered energetically costly parasites (East et al, ; Seguel & Gottdenker, ; Shrestha et al, ). We test predictions derived from six hypotheses: (a) the resource allocation hypothesis of life‐history theory expects high‐ranking juveniles to have lower infection loads than low‐ranking juveniles, because they should have more resources to allocate to immune processes.…”
Section: Introductionmentioning
confidence: 99%
“…Synergistic effects have been described for C. suis and toxigenic Clostridium perfringens where timely anticoccidial treatment also alleviated the effects of clostridiosis [26], showing that C. suis infections promote adhesion of clostridia to the intestinal mucosa, exacerbating the effects of bacterial infection. Preliminary studies also indicated that infections with C. suis alter the succession of bacterial communities in neonatal pig gut, delaying the establishment of lactobacilli (as reviewed in [37]). As interactions between microbiota and the immune system are key to the development of a functional immune system [40] such events may have lasting effects on the development of intestinal and immune functions.…”
Section: Background - Vaccines Against Parasitesmentioning
confidence: 99%
“…In addition, dysbiosis may contribute to increased morbidity (see above) and require antibiotic treatment [7]. Good control of oocyst excretion and coccidiosis-related diarrhoea is achieved by metaphylactic treatment of piglets on the third to fifth day of life with a single dose of toltrazuril (20 mg/kg of body weight) but recently questions about the sustainability of “blanket treatment” of piglets in terms of resistance and drug residues in meat have risen (see [37]), and a call for alterative control strategies has been voiced.…”
Section: Background - Vaccines Against Parasitesmentioning
confidence: 99%